Ecological Network Construction and Optimization in the Southwest Alpine Canyon Area of China Based on Habitat Quality Assessment - Xiran Chen; Jiayue Xiong; Yinghui Guan; Jinxing Zhou (Remote Sensing)
The Southwest Alpine Canyon Area (SACA) is a typical ecologically sensitive location in China; therefore, constructing and optimizing an ecological network for this area is essential to ensure the regional ecological security of its fragile ecosystems. This study employed the InVEST model to quantitatively assess the habitat quality of the SACA for the years 2000, 2010, and 2020. The ecological sources were determined based on the results of a habitat quality assessment and a Morphological Spatial Pattern Analysis (MSPA). Finally, ecological corridors, ecological pinch points, and ecological barrier points were identified using circuit theory. The results indicated that the SACA’s habitat quality was relatively good, but experienced slight degradation from 0.87 in 2000 to 0.84 in 2020. Anthropogenic activities have been identified as the primary contributor to habitat quality decline in the region. Geographically, the habitat quality is significantly poorer in the southeast and northwest of the SACA. A total of 319 ecological sources were identified, predominantly located in the southwest and northeast of the SACA, comprising 43.27% of the total area. Furthermore, 94 ecological corridors were delineated, covering an area of 74,015.61 km2 and extending over 182.80 km in length in total. A total of 38 ecological pinch points and 39 ecological barrier points were distinguished, with a noticeable concentration in regions undergoing ecological degradation. Overall, while the ecological network structure in the SACA is complex and highly interconnected, it faces challenges relating to material cycling and ecological network circulation. Future ecological restoration and protection efforts should focus on areas along the border between the ecological maintenance area in southeastern Tibet (Region I) and the water conservation area in eastern Tibet–western Sichuan (Region II). Additionally, the establishment of ecological protection belts around potential ecological corridors is proposed to enhance ecosystem connectivity. These findings could provide a robust scientific foundation for territorial spatial planning, ecological preservation, and restoration in the SACA.